Midzone microtubule bundles are continuously required for cytokinesis in cultured epithelial cells [published erratum appears in J Cell Biol 1996 Dec;135(6 Pt 1):1679] (The Rockefeller University Press, 1996)
The current model of cytokinesis proposes that spindle poles and associated microtubules determine the cleavage plane, and, once the signal has been delivered to the cortex, the entire mitotic apparatus can be removed without affecting cell division. While supported by compelling data from Echinoderm embryos, recent observations suggest that the model may not be universally applicable. In this study, we have examined the relationship(s) among microtubules, chromosomes, and cleavage activity in living normal rat kidney (NRK) cells with multipolar mitotic figures. We found that cleavage activity correlated with the distribution of midzone microtubule bundles and Telophase Disc 60 protein (TD60) rather than the position of spindle poles. In addition, reduction of midzone microtubules near the cortex, by either nocodazole treatment or spontaneous reorganization in tripolar cells, caused inhibition or regression of furrowing. These results demonstrate that continuous interaction between midzone microtubule bundles and the cortex is required for successful cleavage in tissue culture cells.